Estimating the water supply capacity of Hwacheon reservoir for multi-purpose utilization - Lee, Eunkyung; Lee, Seonmi; Ji, Jungwon; Yi, Jaeeung; Jung, Soonchan (Journal of Korea Water Resources Association, 2022)
In April 2020, the Korean government decided to operate the Hwacheon reservoir, a hydropower reservoir to supply water, and it is currently under pilot operation. Through the pilot operation, the Hwacheon reservoir is the first among the hydropower reservoirs in Korea to make a constant release for downstream water supply. In this study, the water supply capacity of the Hwacheon reservoir was estimated using the inflow data of the Hwacheon reservoir. A simulation model was developed to calculate the water supply that satisfies both the monthly water supply reliability of 95% and the annual water supply reliability of 95%. An optimization model was also developed to evaluate the water supply capacity of the Hwacheon reservoir. The inflow data used as input data for the model was modified in two ways in consideration of the impact of the Imnam reservoir. Calculating the water supply for the Hwacheon reservoir using the two modified inflows is as follows. The water supply that satisfies 95% of the monthly water supply reliability is 26.9 m3/sec and 24.1 m3/sec. And the water supply that satisfies 95% of the annual water supply reliability is 23.9 m3/sec and 22.2 m3/sec. Hwacheon reservoir has a maximum annual water supply of 777 MCM (Million Cubic Meter) without failure in the water supply. The Hwacheon reservoir can supply 704 MCM of water per year, considering the past monthly power generation and discharge patterns. If the Hwacheon reservoir performs a routine operation utilizing its water supply capacity, it can contribute to stabilizing the water supply during dry seasons in the Han River Basin.
Keywords: Hwacheon reservoir; Optimization technique; Simulation technique; Water supply capacity; Water supply reliability